EFEKTIVITAS MENGKONSUMSI BUBUR KACANG HIJAU TERHADAP PRODUKSI ASI - Nurlela, Nurlela; Ekdeni Aifa, Wira; Mardiya, Rizka; Fitria, Nurhidaya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Exclusive breastfeeding is essential for the survival of the child and protects him from various diseases. However, the WHO has stated that the most common reason why mothers stop giving exclusive breastfeeding is because they feel that their milk is not enough for their baby's needs. About 35% of mothers stop exclusively breastfeeding in the weeks after giving birth because they feel that their milk is not enough and their babies are not full. This study aims to analyze the effectiveness of consuming mung bean pulp on breast milk production. This study is a pre-experimental research designed by one group pre test- post test design. The population of all mothers breastfeeding babies 0 to 6 months in Rantau Kasih Village is 31 people. The research sample was 17 people. Sampling technique with Purposive sampling. The research will be carried out in July 2025. Research instrument with questionnaire sheets. The analysis used was univariate and bivariate analysis with Wilcoxon test. Univariate results were obtained: the average value of smooth breast milk production of the respondents before being given an intervention in the form of giving mung bean pulp was 4.65 with a minimum value of 1 and a maximum of 8. After being given an intervention, there was an increase in the average value of the smooth milk production of the respondents to 8.18 with a minimum value of 6 and a maximum of 10. The results of the bivariate test with the Wilcoxon test obtained a value of P=0.000<0.05. In conclusion, there is an effectiveness of consuming mung bean porridge on breast milk production in Rantau Kasih Village, the work area of the UPT Sungai Pagar Health Center.